Arduino Controller Based 3-Switch Isolated DC-DC Boost Converter for PV and Battery Application. Issue 1 (August 2021) - William Christopher, I.; Jones Priya, J.; Raghul, Axin X; Vignesh Kumar, P.; Vimal Raj, S.
Abstract: This paper discusses a Arduino controlled 3-switch Isolated DC-DC Boost converter for PV and battery application. The presented converter has vital benefits such as a switch reduction, snubber circuit elimination with an additional diode, a capacitor; obtain the same primary and secondary voltage waveforms of the transformer with duty cycle variation. The MATLAB Simulink model of the presented converter for 95W PV system has been developed for 20V dc input. The hypothetical forecasts and the performance of the PV based presented converter has been effectively confirmed with the aid of simulation results. The experimental setup of the presented converter for 100W PV module has been successfully implemented using Arduino Uno microcontroller to confirm the simulation outcomes.